Pharmacogenetic substantiation of personalized prescription of oral anticoagulants in clinical practice - K.I. Bentsionova; Z.I. Rossokha; O.G. Ievseienkova; N.G. Gorovenko (Medičnì Perspektivi, 2023)
Thromboembolic diseases are of great clinical concern because of their high prevalence and consequences, which are often fatal. Despite significant progress in the prevention and treatment of thrombotic events, patients remain at risk of life-threatening bleeding episodes and other side effects arising from anticoagulant therapy, so the issue of personalizing prescriptions taking into account the genetic characteristics of patients has become urgent. The purpose of the study is to substantiate the need for patient genotype analysis in order to increase the effectiveness and safety of individual pharmacotherapy. The article has a conceptual nature, therefore the following research methods were chosen: systematization and generalization; analysis and specification; abstract and logical. For the search, we used PubMed, PubMedCentral, Google Scholar, dbSNP, Elsevier, Springer from September 2000 to November 2022. The review included studies written in English and Ukrainian. There were analyzed literature data on two main subclasses of oral antithrombotic agents, including oral anticoagulants and antiplatelet agents, namely warfarin, apixaban, rivaroxaban, and clopidogrel. Prognostically significant for evaluating the effectiveness and safety of anticoagulant use, as well as the most studied in this aspect, are CYP2C9 (rs1799853, rs1057910), CYP2C19 (rs4244285, rs4986893, rs12248560), VKORC1 (rs9923231, rs7294, rs9934438), MDR1 (rs4148738, rs2032582, rs1045642), FGB (rs1800787), PAI-1 (rs1799889) genes. The results of CYP2B6, CYP3A4/5 (rs776746), CYP4F2 (rs2108622) genes analysis indicate a certain influence on the anticoagulants metabolism and require further detailed study. Factors such as age, race, sex, smoking, diet, and other medications are known to influence the effectiveness of antithrombotic therapy, but the most influential factor is genetics, which accounts a significant percentage of interindividual variability. Future research should focus on the study of known and novel genetic variants that influence drug metabolism, as well as the molecular mechanisms that contribute to changes in plasma anticoagulant levels. The article provides a brief overview of action mechanisms, pharmacogenetics, and interactions between drugs and the genes responsible for their metabolism. The results indicate the need for studies of gene variants considered in this review before starting anticoagulant therapy, and attention should also be paid to the possibility of inhibitors and inductors influence on components of the metabolic pathway of anticoagulants and gene expression products that participate in their metabolism. The totality of these measures will ensure an increase in the efficiency and safety of individual pharmacotherapy and allow optimizing the choice and dosage of anticoagulants.